Breast Milk‐Derived Limosilactobacillus reuteri Prevents Atopic Dermatitis in Mice via Activating Retinol Absorption and Metabolism in Peyer's Patches. Issue 2 (8th December 2022) - Qi, Ce; Tu, Huayu; Zhao, Yuning; Zhou, Jingbo; Chen, Jie; Hu, Haiting; Yu, Renqiang; Sun, Jin
Abstract : Scope: Supplementing Limosilactobacillus reuteri Fn041, a breast milk‐derived probiotic from agricultural and pastoral areas, to maternal mice during late pregnancy and lactation prevents atopic dermatitis (AD) in offspring. This study aims to elucidate the molecular mechanism of Fn041‐mediated immune regulation. Methods and results: Fn041 is administered prenatal and postnatal to maternal mice, and to offspring after weaning. The ears are administered with calcipotriol to induce AD. Fn041 treatment significantly alleviates ear inflammation, and reduces mast cell infiltration. Fn041 treatment upregulates and downregulates intestinal ZO‐1 and Claudin‐2 mRNA expression, respectively. Transcriptome analysis of Peyer's patches reveals that pathways related to DNA damage repair are activated in AD mice, which is inhibited by Fn041 treatment. Fn041 activates pathways related to retinol absorption and metabolism. Untargeted metabolomic analysis reveals that Fn041 treatment increases plasma retinol and kynurenine. Fn041 treatment does not significantly alter the overall cecal microbiota profile, only increases the relative abundances of Ligilactobacillus apodemi, Ligilactobacillus murinus, Akkermansia muciniphila, and Bacteroides thetaiotaomicron . Conclusions: Fn041 induces anti‐AD immune responses directly by promoting the absorption and metabolism of retinol in Peyer's patches, and plays an indirect role by strengthening the mucosal barrier and increasing the abundance of specific anti‐AD bacteria in the cecum. Abstract : Limosilactobacillus reuteri Fn041 activates the pathway of retinol absorption and metabolism at Peyer's patches in the small intestine of mice, thereby inducing immune tolerance and preventing the occurrence of atopic dermatitis.